Frog and Toad are friends - Lobel, Arnold ([New York] : HarperCollins Publishers, 1970)
Five tales recounting the adventures of two best friends--Frog and Toad.
Caldecott Medal/Honor.
Notable/Best Books (A.L.A.).
Wilson's Children.
Book Links (A.L.A.), November 1998.
Booklist, September 2007.
Bulletin (Center for Children's books), February 2006.
Keywords: Friendship -- Fiction; Frog (Fictitious character : Lobel) -- Fiction; Frogs -- Fiction; Toad (Fictitious character : Lobel) -- Fiction; Toads -- Fiction; Friendship -- Fiction; Frog (Fictional character : Lobel) -- Fiction; Frogs -- Fiction; Toad (Fictional character : Lobel) -- Fiction; Toads -- Fiction; Readers (Elementary).